Implementasi Algoritma Floyd Warshall dalam Pencarian Rute Terpendek Lokasi Tower Base Transceiver Station (BTS) pada PT Citra Akses Indonusa - Savitri, Bella Nafa; Jauhari, Mohammad Nafie; Alisah, Evawati; Fahmi, Hisyam (Mathematics Department, Maulana Malik Ibrahim State Islamic University of Malang, 2023)
PT Citra Akes Indonusa is a company that operates on the expertise of information technology services in Banten Province. One of the services provided by the company requires the construction of a Base Transceiver Station (BTS) tower. The tower requires maintenance if there is damage to the network signal. As a result, the shortest route is needed to make it easier for employees to reach the tower location to be more effective. There are eight BTS tower locations in Tangerang Regency and three BTS tower locations in Tangerang City. The process of finding the shortest route in this study uses the Floyd Warshall algorithm, which is unique in finding the shortest route by comparing each edge of all edges that are passed. The process of testing the shortest route is done by selecting the starting point, then selecting several BTS tower locations. Next, the shortest route will be searched using the Floyd Warshall algorithm from each point of destination for the BTS tower location, then the BTS tower location will be selected first and so on until the last destination. The effectiveness of this shortest route search involves a comparison of the routes presented by Google Maps. Based on the results of 30 randomized trials on BTS tower locations, the average shortest route effectiveness was 25.54% compared to the route generated by Google Maps. This is due to the selection at each BTS tower destination location so as to make the route more effective.